Are Video Games Killing the Classroom Star? Adolescent Gaming, Wellbeing and Academic Performance in South Africa - Van Wyk, Francois Jaco (Stellenbosch : Stellenbosch University, 2026)
Thesis (MA)--Stellenbosch University, 2026.